(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The proliferation of civilization, industry, and urbanization, along with population growth, has contributed significantly to the generation of waste materials, and this trend continues to this day. Such waste has far-reaching impacts on both human health and the environment, leading to environmental degradation and rendering it non-environmentally friendly. To address these concerns, many scientists have directed towards the possibility of using waste materials as a substitute for some components of the concrete mixture. Numerous studies have demonstrated the effectiveness of incorporating such materials such as (coal bottom ash (CBA), waste plastic and fibers, wood waste, and soft drink bottle caps) in enhancing concrete’s properties, including durability, compressive and tensile strength, water content, slump flow, and suitability for reuse in engineering projects. The use of such materials not only provides an economic solution but also promotes environmental preservation by mitigating environmental problems.